PENGARUH CORPORATE GOVERNANCE TERHADAP CAPITAL STRUCTURE (Studi pada Perusahaan Manufaktur yang Terdaftar di BEI) - Francisca Bulan; Etna Nur Afri Yuyetta (Diponegoro Journal of Accounting, 2014)
The aim of this research is to analyze the effect of corporate governance on capital structure. Companies are required to establish rigorous in combined debt and equity (capital structure) to create an optimal capital structure for the company. Determining capital structure can not be separated from the stakeholders who have interest against the company. The close relationship between capital structure with stakeholders triggering the need for a mechanism that ensures the interests of stakeholders. Corporate governance appears as a series of mechanisms that direct and control a corporation that runs the company's operations in accordance with the expectations of the stakeholders. Corporate governance used in this study is board size, remuneration of directors, meetings of directors, and audit committee. This study was conducted using data companies listed in Indonesia Stock Exchange (IDX ) 2010-2012. The sampling method in this research is purposive sampling, the amount of samples are 88 samples. Hypothesis testing is done by using multiple regression analysis.The results of this study indicate that board meeting has positive influence to the capital structure. While the other variable such as board size, remuneration of directors, and audit committee are not significantly affected to capital structure.